The Effect of Principal Leadership and Teacher Competence on Teacher Performance with Learning Management as a Mediating Variable - Siti Yuli Chulaelah; Setya Raharja (Lembaran Ilmu Kependidikan, 2025)
Background - Teacher competencies include pedagogic, professionalism, social and personality. However, there are still many problems faced regarding the development and implementation of these competencies in schools. Purpose - This study aims to describe the effect of principal leadership and teacher competence on teacher performance with learning management as a mediating variable. Method/approach - The approach used in this research is quantitative with a correlational design. Findings - The results showed that: (1) principal leadership has a positive but insignificant effect on performance, T-count = 0. 943 and p-value = 0.346; (2) learning management has a positive and significant effect on teacher performance, T-count = 6.261 and p-value = 0.000; (3) teacher competence has a positive and significant effect on teacher performance, T-count = 6.033 and p-value = 0.000; (4) principal leadership, learning management, and teacher competence simultaneously have a positive and significant effect on teacher performance, R-square = 0.684 and SRMR = 0.064; (5) through the mediation path on learning management it is found that leadership indirectly has a positive and significant effect on teacher performance, T-count = 4.510 and p-value = 0.000; (6) through the mediator of learning management it is found that teacher competence indirectly has a positive and significant effect on teacher performance, T-count = 17.477 and p-value = 0. 000. Improving teacher performance is expected to be followed up with concrete steps through various competency improvement programs, training, and relevant policy improvements. Conclusion – Learning management plays a crucial mediating role in enhancing the impact of both leadership and competence on teacher performance. Strengthening this variable is key to improving teacher outcomes in schools. Novelty/Originality/Value – This study contributes to the literature by empirically validating learning management as a significant mediating factor between leadership, competence, and teacher performance—a relationship that is rarely explored in previous studies. The integration of leadership, competence, and instructional management provides a comprehensive model for improving educational quality.